Increased innate immune responses by interleukin-22 contributes to the inflammatory process in rheumatoid arthritis. (22nd February 2012) - Marijnissen, Renoud J; Koenders, Marije I; Nickerson-Nutter, Cheryl; Abdollahi-Roodsaz, Shahla; Boots, Annemieke M H; Joosten, Leo A B; van den Berg, Wim B
Abstract : Backgroundand objectives: IL-22 is a mediator in antimicrobial responses and inflammatory autoimmune diseases. It can be produced by innate and adaptive haematopoietic immune cells, but the expression of the receptor (IL-22R) seems to be restricted to non-haematopoietic tissue cells. Although both IL-22 and the IL-22R have been identified in the synovium of RA patients, the contribution to disease pathogenicity remains to be established. Materials and methods: The authors first investigated the expression and origin of IL-22 and the IL-22R in the inflamed joints of IL-1Ra-/- mice. Furthermore, the mice were treated with neutralising anti-IL-22 antibodies. Subsequently, the authors analysed the IL-22R expressing cells in human RA synovium by immunohistochemistry (IHC) and flow cytometry. Eventually, the authors stimulated RA synovial biopsies, RA human fibroblast-like cells (RAFLS) and endothelial (HUVEC) cells with IL-22 and analysed the production of inflammatory mediators. Results: In the arthritic joints of IL-1Ra-/- mice, IL-22 is mainly produced by T cells that co-expressed IL-17. Anti-IL-22 treatment of IL-1Ra-/- mice significantly reduced inflammation and bone erosion, suggesting an important role of IL-22 in joint destruction. The authors subsequently analysed the effects of IL-22 on human RA synovium. Exposure to IL-22 increased the expression of TNFα, IL-6 and IL-8. Compared to IL-17, stimulation with IL-22 induced higher levels of IL-8, and combination of the two cytokines resulted in an additional response. IHC identified endothelial cells and synovial fibroblast-like cells as the main IL-22 receptor expressing cells. Surprisingly, stimulation of RA human fibroblast-like cells and endothelial (HUVEC) cells did not result in a clear increase in the innate immune response. This in contrast to the synovial tissue, which is heavily infiltrated with inflammatory cells. Conclusions: Our data support the dual role of IL-22 in pathological inflammation, showing that the functional importance of IL-22 is context dependent. Current SCID studies with neutralising IL-22 antibodies will have to prove the therapeutic potential of IL-22 in RA.